ANALISA KELAYAKAN INVESTASI PROYEK PEMBANGUNAN PERUMAHAN BERLIAN KUOK SEJAHTERA - Taufik, Hendra; Larici, Ria (Proceedings ACES (Annual Civil Engineering Seminar), 2015)
Project Housing development has growing fast in Pekanbaru. It is not only in the central citybut also in the suburbs area. PT Tiga Berlian Sejahtera is developing housing project at Jl.Pekanbaru-Bangkinang, Rimbo Panjang, Kampar Regency. The objective of this research isBerlian Kuok sejahtera’s housing with 3 Ha area and 141 housing units will be marketed. Thisconstruction by using alternative is 30% equity and 70% loan. The purpose of this thesis is todetermine investment feasibility of project housing development Berlian Kuok Sejahtera withindicator of investment feasibility using method Net Present Value (NVP), Benefit Cost Ratio(BCR), and Internal Rate of Return (IRR). Then, sensitivity level will be tested of investment,interest rate, benefit, and cost. From the financial terms, the return on investment with a periodof 3 years can be fulfilled with a value of NPV Rp 2.141.123.359,44, IRR amount to 20,42%,and the BCR at 1,07. From the sensitivity analysis, housing development Berlian KuokSejahtera still feasible to limit investment costs increased to 11,32%, the interest rate increasedto 63,38%, the sensitivity of benefit decreased 9,47% and sensitivity of cost increased by136,34%.Kata kunci: housing development, investment feasibility, BCR, IRR, NVP, sensitivity